2021
DOI: 10.1021/acs.orglett.1c02715
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Synthesis of Tricyclic Indoles via a N–S Bond Cleavage Strategy

Abstract: In palladium/norbornene (Pd/NBE) chemistry, the “ortho effect” has been proven to be a key factor in the process of β-carbon elimination to extrude NBE. Herein, we found that the o-iodoaniline protected by a p-methoxybenzenesulfonyl group can recover the “ortho effect” and then undergo N–S bond cleavage with vinyl palladium, thus achieving a highly selective C–N coupling reaction in the Catallani–Lautens reaction system. On the basis of this discovery, a one-step synthesis of highly functionalized tricyclic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Seminal works by Catellani, Lautens, Dong, Gu, Liang, Luan, and other groups [ 57 ] revealed that a series of polysubstituted aromatics, carbocyclic, and heterocyclic compounds could be obtained by Pd/NBE-catalyzed difunctionalization of aryl halides. In 2021, Zhang, Liang, Li, Quan, and co-workers [ 58 ] disclosed an elegant method for the synthesis of 3,4-fused tricyclic indoles via a N–S bond cleavage strategy in one step using palladium and NBE in a co-catalysis ( Scheme 16 ). After extensively screening different amino protecting groups, para -methoxy benzenesulfonyl was used as the optimal protecting group, giving the desired product in moderate yield.…”
Section: Intermolecular Cyclizationmentioning
confidence: 99%
“…Seminal works by Catellani, Lautens, Dong, Gu, Liang, Luan, and other groups [ 57 ] revealed that a series of polysubstituted aromatics, carbocyclic, and heterocyclic compounds could be obtained by Pd/NBE-catalyzed difunctionalization of aryl halides. In 2021, Zhang, Liang, Li, Quan, and co-workers [ 58 ] disclosed an elegant method for the synthesis of 3,4-fused tricyclic indoles via a N–S bond cleavage strategy in one step using palladium and NBE in a co-catalysis ( Scheme 16 ). After extensively screening different amino protecting groups, para -methoxy benzenesulfonyl was used as the optimal protecting group, giving the desired product in moderate yield.…”
Section: Intermolecular Cyclizationmentioning
confidence: 99%
“…For example, in 2021, Quan reported the synthesis of tricyclic indoles via a palladium-catalyzed NÀ S bond cleavage reaction. [21] Recently, Luo and co-workers developed a method of visible-light-driven iridium-catalyzed NÀ S bond activation of sulfonamides through a radical pathway. [22] Some approaches for CÀ N bond activation have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…The Au-catalyzed cycloisomerization of 1,5-enynes efficiently afforded bicyclo[3.1.0]­hexene 7n in 91% yield with >99% ee and 12:1 dr . Moreover, tricyclic indole derivative 8n was synthesized via a palladium-catalyzed cascade process in 52% yield without the loss of enantioselectivity . Finally, a chemo- and regioselective hydroboration–oxidation sequence, followed by O- tosylation and cyclization with BnNH 2 as a lynchpin, afforded 4,5-disubstituted azepane 9n in good yield and excellent enantioselectivity.…”
mentioning
confidence: 99%